2019
DOI: 10.3390/su11051373
|View full text |Cite
|
Sign up to set email alerts
|

Ksar Said: Building Tunisian Young People’s Critical Engagement with Their Heritage

Abstract: This paper describes the work undertaken as part of the ‘Digital Documentation of Ksar Said’ Project. This project, funded by the British Council, combined education, history, and heritage for the digital preservation of tangible and intangible aspects of heritage associated with the 19th century Said Palace (Ksar Said) in Tunis. We produced an interactive 3D model of Ksar Said and developed learning resources to build Tunisian students’ critical engagement with their heritage through inquiry learning activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Although it is complex in its various parts, we have simultaneously developed generic tools (see description in note 1), including a how-to guide for the creation of dialogic chatbots, to enable others to experiment in other contexts -playing with their content, adjusting how, in which order and when (if at all) they are deployed, and otherwise remixing them, knowing that individually and collectively they function to enhance emotive outcomes among users. Our tests of the pre/historical empathy model suggest that it is best applied in informal educational environments, owing to the challenges of integrating any new resource into the formal learning setting (also see comparable discussions in Di Giuseppantonio Di Franco et al (2019) and Hiriart (2019)). While this point requires further exploration (see McKinney et al, forthcoming), the informal application of this approach is arguably its strength, as young people are empowered to survey ideas that might otherwise sit awkwardly within their formal schooling, and that might more fluidly fold into their home lives, where empathetic (or non-empathetic) relations are so strongly created and reinforced.…”
Section: Pre/historic Empathy Through Dialogue: Emotive's Digital Edumentioning
confidence: 79%
See 1 more Smart Citation
“…Although it is complex in its various parts, we have simultaneously developed generic tools (see description in note 1), including a how-to guide for the creation of dialogic chatbots, to enable others to experiment in other contexts -playing with their content, adjusting how, in which order and when (if at all) they are deployed, and otherwise remixing them, knowing that individually and collectively they function to enhance emotive outcomes among users. Our tests of the pre/historical empathy model suggest that it is best applied in informal educational environments, owing to the challenges of integrating any new resource into the formal learning setting (also see comparable discussions in Di Giuseppantonio Di Franco et al (2019) and Hiriart (2019)). While this point requires further exploration (see McKinney et al, forthcoming), the informal application of this approach is arguably its strength, as young people are empowered to survey ideas that might otherwise sit awkwardly within their formal schooling, and that might more fluidly fold into their home lives, where empathetic (or non-empathetic) relations are so strongly created and reinforced.…”
Section: Pre/historic Empathy Through Dialogue: Emotive's Digital Edumentioning
confidence: 79%
“…In contrast to the passive, didactic and solitary pedagogical techniques that are the basis of many of the resources discussed above, we suggest that a humanfocused practice, such as archaeology, requires a human-focused pedagogy. The concept of historical empathy offers a meaningful intellectual grounding upon which to build such a pedagogy, and it has obvious parallels with both the inquiry-based approach of Di Giuseppantonio Di Franco et al (2019) and the historical thinking approach of Hiriart (2019). Collectively, these models seek to nurture richer personal engagements with heritage through methods that oblige students to see -or, indeed, embody -difference and to take the lead in navigating their own learning.…”
Section: The Argument For Pre/historical Empathymentioning
confidence: 99%
“…She found that using digital recording in archaeology freed up time, allowing "a new form of local, intergenerational knowledge production between myself, Abiquiú youth interns, and their families" as they created analog collages and zines alongside digital records of archaeological remains (Danis 2019, p. 388). Multimodality also has resonance with practice-based research and the continual discussions regarding technologies and creative practice (Beale & Reilly 2017) and in cocreation (Di Giuseppantonio Di Franco et al 2019) and enchantment (Perry 2019); as such, archaeologists could join what is already a vibrant discussion in anthropology.…”
Section: Discussionmentioning
confidence: 99%
“…There are many educational benefits to integrating VR technologies with traditional teaching methods. For example, using VR in a blended learning environment allows for teacher-student discussion and is seen as an effective for of inquiry-based learning [36]. VR enables critical learning opportunities in an entertaining and engaging process [37].…”
Section: Immersive Technologies As Learning Toolsmentioning
confidence: 99%